Optimal genotype × environment × management as a strategy to increase grain maize productivity and water use efficiency in water-limited environments and rising temperature. (December 2019) - Rahimi-Moghaddam, Sajjad; Kambouzia, Jafar; Deihimfard, Reza
Highlights: Ignoring adaptation strategies under climate change caused extreme reduction in maize grain yield in the future. Sustainability can be obtained for maize cropping systems through the choice of an optimal G × E × M in the future. The optimal genotype × management for winter and summer seasons would be SC260 × 10-time irrigation per crop season and SC704 × 10-time irrigation per crop season in 2050, respectively. Shifting from winter cultivation to summer sowing in the future could benefit for maize cropping system. Abstract: Water limitation is a major concern for the present and future of agriculture, particularly in fragile areas such as arid and semi-arid regions under climate change conditions. In such ecosystems, sustainability of maize production can partially be achieved by investigating the interaction of genotype, environment and management, particularly as effected by climate change. The Agricultural Production Systems sIMulator (APSIM) was applied to assess the effect of future climate change on maize grain yield and water use efficiency in Khuzestan province for two cultivars (as genotype), two seasons (as environment) and nine irrigation regimes (as management). Projections of future climate of Khuzestan was conducted using the baseline period of 1980–2010 and Miroc5 general circulation model for 2040–2070 under two RCPs using The Agricultural Model Intercomparison and Improvement Project (AgMIP) methodology at 15 locations. The simulation results demonstrated that grain yield and water use efficiency will have decreased 6.04% and 5.4%, respectively across the province in 2050 under both RCP4.5 and RCP8.5. This decrease can be mitigated and sustained by adapting a suitable genotype × environment × management interaction. The optimal genotype × environment × management for winter and summer seasons were SC260 × winter sowing × 10-time irrigation per crop season and SC704 × summer sowing × 10-time irrigation per crop season, respectively. Shifting from winter maize cultivation to summer sowing in the future could result in a change in environmental conditions that include a reduced mean temperature (−2.6 °C) and an increase rainfall (81.3 mm) and length of maize growing season (7.9 days). This will reduce water consumption by maize by 185.37 mm, increase water use efficiency by 4.38 kg ha −1  mm −1 and grain yield by 88.32 kg ha −1 . The results show that sustainability can be obtained for maize cropping systems through the choice of an optimal genotype × environment × management in the forthcoming period.